Envolvimento do estresse oxidativo nas convulsões induzidas por disseleneto de difenila em ratos jovens - Prigol, Marina (2007)
Seizures can occur at any age, affecting at least 1-2% of the world population, they are far more common in children than adults. Prolonged seizures in the early developmental period can cause brain damage and lead to serious consequences later in life. In the present study the potential neurotoxicity of diphenyl diselenide, as measured by the manifestation of seizures in rat pups (postnatal day, PND, 12-14) was evaluated. The results suggest that the latency for the appearance of tonic-clonic seizures, characterized by rearing and falling of rat pups body, was dependent of the dose tested. Diphenyl diselenide at high doses induced seizure episodes in rat pups. The highest dose of diphenyl diselenide (500mg/kg) increased the levels of lipid peroxidation and catalase activity as well as decreased d-ALA-D (d-aminolevulinate dehydratase) and Na+, K+-ATPase activity in brain of rat pups. Our results indicate the possible involvement of free radical oxygen injury in diphenyl diselenide-induced seizures. The data obtained with the dose of 150 mg/kg in the brain of rats that exhibiting seizures are: an increase in lipid peroxidation levels; the lack of effect on catalase activity; an inhibition of d-ALA-D activity, supporting that the enzyme activity is more sensitive than other parameters analyzed as an indicator of oxidative stress. The lowest dose of diphenyl diselenide in brain emphasizes the relationship between the appearance of seizures and the latency for the onset of the first episode. Taken together, this paper could add to our understanding of diphenyl diselenide neurotoxic effect demonstrated by the appearance of seizures which are, at least in part, related to the oxidative stress.